Robotic Exploration of the Solar System Part 3: Wows and Woes, 1997-2003 - Ulivi, Paolo; Harland, David M.; SpringerLink (Online service) (New York, NY : Praxis : Imprint: Praxis, 2012)
In Robotic Exploration of the Solar System, Paolo Ulivi and David Harland provide a comprehensive account of the design and managment of deep-space missions, the spacecraft involved - some flown, others not - their instruments, and their scientific results. This third volume in the series covers launches in the period 1997 to 2003 and features: - a chapter entirely devoted to the Cassini-Huygens mission to Saturn; - coverage of planetary missions of the period, including the Deep Space 1 mission and the Stardust and Hayabusa sample returns from comets and asteroids; - extensive coverage of Mars exploration, the failed 1999 missions, Mars Odyssey, Mars Express, and the twin rovers Spirit and Opportunity. The story will continue in Part 4.
(In Part 1) Introduction -- Chapter 1: The beginning -- Chapter 2: Of landers and orbiters -- Chapter 3: The grandest tour -- (In Part 2) Chapter 4: The decade of Halley -- Chapter 5: The era of flagships -- Chapter 6: Faster, cheaper, better -- (Now in Part 3) Foreword -- Author's Preface -- Acknowledgments -- Chapter 7: The last flagship -- Chapter 8: Faster, cheaper, better continues -- Chapter 9: Mars invaded -- Glossary -- Appendices -- Chapter references -- Further reading -- Previous volumes in this series -- Index.
Keywords: Science (General).; Astronomy; Astrophysics; Astrobiology; Astronautics; Popular Science; Popular Science in Astronomy; Astronomy, Astrophysics and Cosmology; Extraterrestrial Physics, Space Sciences; Astrobiology; Aerospace Technology and Astronautics